2015
DOI: 10.1007/s11418-015-0955-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitative analysis of 12 methoxyflavones with melanogenesis inhibitory activity from the rhizomes of Kaempferia parviflora

Abstract: A methanol extract from the rhizomes of Kaempferia parviflora Wall. ex Baker (Zingiberaceae) has shown inhibitory effects against melanogenesis in theophylline-stimulated murine B16 melanoma 4A5 cells (IC50 = 9.6 μg/mL). Among 25 flavonoids and three acetophenones isolated previously (1-28), several constituents including 5-hydroxy-7,3',4'-trimethoxyflavone (6, IC50 = 8.8 μM), 5,7,3',4'-tetramethoxyflavone (7, 8.6 μM), 5,3'-dihydroxy-3,7,4'-trimethoxyflavone (12, 2.9 μM), and 5-hydroxy-3,7,3',4'-tetramethoxyfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…B16 cells (8 × 10 3 cells/well) were seeded into 48‐well plates in DMEM. After preculture with samples (100 μmolL −1 ) and theophylline (1 mmolL −1 ) for 72 hours, melanin contents in cells were measured according to the protocol described previously …”
Section: Methodsmentioning
confidence: 99%
“…B16 cells (8 × 10 3 cells/well) were seeded into 48‐well plates in DMEM. After preculture with samples (100 μmolL −1 ) and theophylline (1 mmolL −1 ) for 72 hours, melanin contents in cells were measured according to the protocol described previously …”
Section: Methodsmentioning
confidence: 99%
“…Thailand is recognized as a center of diversity, and distribution to different region of Asia [22]. In previous studies, 25 methoxyflavones and their glycosides were identified and quantified as predominant flavonoids from rhizome extracts (Supplementary Table 2) [23][24][25][26]. The presence of these compounds contributed to a wider range of medicinal effects such as antiinflammatory [27], antioxidant [28,29], antiproliferative activity [30], hepatoprotective effect [31], and anticancer [32].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Several coumarins, [1][2][3][4][5][6][7] xanthones, 8,9) triterpenoids, 10) and steroids 10) have been isolated from the flowers, 1,2,6,7,10) seeds, 3,9) twigs, 4,8) and bark 5) of this plant. In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells.…”
mentioning
confidence: 99%
“…In the course of our characterization studies on bioactive constituents in Thai natural medicine, 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we reported that the methanol extract of the flowers of M. siamensis and its coumarin constituents showed inhibitory effects on nitric oxide production in lipopolysaccharide-activated RAW264.7 cells. 1) Further studies revealed that the methanol extract inhibited enzymatic activity against aromatase.…”
mentioning
confidence: 99%